Inclusion and Neighborhood Properties for Certain Classes of Multivalently Analytic Functions. (10th November 2013) - Bulut, Serap
Abstract : We introduce and investigate two new general subclasses of multivalently analytic functions of complex order by making use of the familiar convolution structure of analytic functions. Among the various results obtained here for each of these function classes, we derive the coefficient inequalities and other interesting properties and characteristics for functions belonging to the classes introduced here.